2016
DOI: 10.1002/pc.23947
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation properties of melt processed PBS/chitosan bio‐nanocomposites with silica, silicate, and thermally reduced graphene

Abstract: Melt processed bio-nanocomposites of poly(butylene succinate) (PBS)-chitosan (CS) generated with varying amounts of silica, alumina-silicate, and thermally reduced graphene were analyzed for their biodegradation behavior. The nanocomposite samples were embedded in soil under natural environment for varying periods of time and the weight loss analysis was complemented with changes in surface morphology, crystallinity, and thermal degradation. Both the type and amount of filler were observed to affect the extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…As the filler content increases, the amount of filler particles localized directly on the sample surface statistically increases, which also increases the roughness. This is a typical result for PBS matrix composites with powder filler [128,129]. The obtained post-ageing roughness results are consistent with the above analysis of the colour results, and the obtained course of changes is directly related to the degradation of the lignocellulosic filler and the mechanical leaching of the products of this degradation [126].…”
Section: Surface Roughnesssupporting
confidence: 88%
“…As the filler content increases, the amount of filler particles localized directly on the sample surface statistically increases, which also increases the roughness. This is a typical result for PBS matrix composites with powder filler [128,129]. The obtained post-ageing roughness results are consistent with the above analysis of the colour results, and the obtained course of changes is directly related to the degradation of the lignocellulosic filler and the mechanical leaching of the products of this degradation [126].…”
Section: Surface Roughnesssupporting
confidence: 88%
“…However, there are signs of lower weight loss than the pure PBS-CS blend. [194] and TiO 2 and polypropylene (PP) nanocomposites show efficient photocatalytic degradation behavior, [195] as well as in blends with ϵ-caprolactone/ DL-lactide (ϵ-CL/DL-LA) copolymers. [196] Table 18 summarizes the state-of-the-art information from the research studies of biodegradable nanocomposites using nano-oxides.…”
Section: A Green Approach Toward Biodegradable Nano-oxide Compositesmentioning
confidence: 99%
“…In blend with PBS‐CS, both silica and alumina have shown signs of degradability, even more compared with graphene particles. However, there are signs of lower weight loss than the pure PBS‐CS blend . and TiO 2 and polypropylene (PP) nanocomposites show efficient photocatalytic degradation behavior, as well as in blends with ɛ‐caprolactone/ dl ‐lactide (ɛ‐CL/ dl ‐LA) copolymers .…”
Section: Nanofillersmentioning
confidence: 99%
“…Iftekhar et al [11] used a XANT-layered double hydroxide nanocomposite to remove metal ions from rare earth elements, obtaining good maxima adsorption capacities (Sc +3 : Qo = 132.30 mg/g, Nd +3 : Qo = 14.01 mg/g, Tm +3 : Qo = 18.15 mg/g, and Yb +3 : Qo = 25.73 mg/g) and finally it has been reported that organic compounds such as trichloroethylene was transformed (65 % from an aqueous solution containing 10 mg/L of this compound) by XANT-zero valent iron particles [12], and bisphenol A was adsorbed by the temperature-sensitive XANT-isopropylacrylamide hydrogel with a high efficiency (Qo = 458 mg/g) [13]. Nonetheless, the XANT-derivatization or synthesis of nanocomposites demand a considerable cost in reagents and energy, and the biodegradability of these compounds is decreased [36][37][38].…”
Section: Introductionmentioning
confidence: 99%